Poverty in India and Indian states: an update - Datt, Gaurav (International Food Policy Research Institute, 1998)
A complete and updated series on poverty measures for India is presented spanning the period 1951–1994. The series are presented at the all-India level as well as for 15 major states, and for rural and urban sectors separately. Key features of the evolution of poverty in India are described.